The cardiovascular complications of diabetes: a striking link through protein glycation - Ahmad Mousa Numan; Farah Amani Ibrahim; Al-Qirim Tareq Musbah (Sciendo, 2020)
Diabetes mellitus is a predominant cause of mortality and morbidity worldwide. One of its serious health problems is cardiovascular complications. Advanced glycation end products (AGEs) are a group of heterogeneous toxic oxidant compounds that are formed after a non-enzymatic reaction between monosaccharides and free amino groups of proteins, compound lipids, and nucleic acids. AGE interacts with various types of cells through a receptor for AGE (RAGE). The interaction between AGE and RAGE is responsible for a cascade of inflammation, oxidative stress, and disruption of calcium homeostasis in cardiac cells of diabetic patients. There is striking evidence that the AGE/RAGE axis with its consequences on inflammation and oxidative stress plays a major role in the development of cardiovascular complications. Therefore, considering AGE as a therapeutic target with foreseeable results would be a wise direction for future research. Interestingly, several studies on nutraceutical, pharmaceutical, and natural products have begun to reveal promising therapeutic results, and this could lead to better health outcomes for many diabetic patients worldwide. This article discusses the current literature addressing the connection between protein glycation and diabetes cardiovascular complications and suggests future avenues of research.